SISTEM ABSENSI GURU BERBASIS WEB DENGAN FRAMEWORK LARAVEL PADA SDN SERUA 03 - Divan Dira Maulana; Hafidh, Muhammad Fadhillah; Pratama, Sidik Yoga; Saputra, Suhanda (Journal of Research and Publication Innovation, 2024)
Information technology has changed many aspects of life, including the education sector, where the consistent presence of teachers is key to effective learning. SDN Serua 3 faces challenges in managing teacher absences which are still done manually, resulting in less than optimal efficiency and accuracy. To overcome this problem, this research developed a web-based teacher attendance system using the Laravel and MySQL frameworks. This system is designed to make it easier to record attendance, increase transparency, and provide reports automatically. Using Laravel, this system provides an organized structure, security, and capabilities for efficient attendance data management. The implementation of this system is expected to increase the efficiency of teacher attendance management at SDN Serua 3, supporting more effective learning.